p53 SUMOylation Mediates AOPP-Induced Endothelial Senescence and Apoptosis Evasion - Chen, Yanjia; Liu, Zhuanhua; Chen, Hongyu; Huang, Xingfu; Huang, Xiaoxia; Lei, Yang; Liang, Qing; Wei, Jiayi; Zhang, Qin; Guo, Xiaohua; Huang, Qiaobing (Frontiers in Cardiovascular Medicine, 2022)
The aging of endothelial cells plays a critical role in the development of age-related vascular disease. We established a model of endothelial premature senescence by application of Advanced oxidation protein products (AOPPs) modified bovine serum albumin (AOPP-BSA) in human umbilical vein endothelial cells (HUVECs). This cellular senescence was accompanied with endothelial barrier dysfunction and angiogenesis impairment. It was further revealed that these senescent HUVECs underwent apoptosis evasion and the receptor for advanced glycation endproducts (RAGE) played a role in these processes. The AOPP-induced senescence was regulated by the state of autophagy in HUVECs. We further proved that AOPP-BSA attenuated the autophagy of HUVECs, led to p53 SUMOylation at K386, resulting in endothelial senescence. We also established the animal model of vascular senescence by using ApoE-/- mice fed with high-fat diet plus daily injection of AOPP-BSA to verify the role of p53 SUMOylation in vascular senescence. Combined with intraperitoneal injection of rapamycin, the effect of autophagy on AOPP-induced p53 SUMOylation was also confirmed in vivo. Our data indicates that p53 SUMOylation at K386 plays an important role in AOPP-induced endothelial senescence and apoptosis evasion, suggesting that p53 K386 SUMOylation may serve as a potential therapeutic target in protecting against vascular senescence.